Laboratory Experimental Studies on the Properties of Highly Sedimentary Lyos Soils when their Moisture Changes Over Time - Pulatovich, Matyokubov Bobur; Innatillayevich, Goyibov Oybek (European Journal of Life Safety and Stability (2660-9630), 2021)
Research on lyoss soils in Central Asia has been going on for a long time. However, these works were mainly descriptive in nature. However, in connection with the rapid development of construction in the lyoss soils of Central Asia, regular fundamental research on lyoss soils is carried out. Lyoss gruts are found in a low-bonded, vigorous, sometimes scattered state. The degree of salinity in them depends on the amount of water-soluble salts in dry soils. Chemical analysis of such soils showed that the gravitational force of the water shells surrounding the hard rocks is 1600-11560 mg/kg, their ions are 180-1410, and sulfate is 620-2530 mg/kg.